Effect of Malnutrition at Diagnosis on Clinical Outcomes of Children With Acute Lymphoblastic Leukemia. Issue 2 (March 2016) - Yazbeck, Nadine; Samia, Loma; Saab, Raya; Abboud, Miguel R.; Solh, Hassan; Muwakkit, Samar
Abstract : Acute lymphoblastic leukemia (ALL) is the most common malignancy among children. Although studies have shown that malnutrition can negatively affect treatment outcome, results are controversial. This retrospective study aims at determining the prevalence of malnutrition and its association with treatment outcome among children with ALL treated at the Children's Cancer Institute in Lebanon. A total of 103 patients diagnosed with ALL between April 2002 and May 2010 were enrolled. Anthropometric data were collected from medical records upon diagnosis, at 3 and 6 months, and at the end of treatment. Body mass index was calculated for children 2 years of age and older, whereas weight-for-height ratio was used for patients below 2 years. Patients were considered underweight, stunted, or wasted if their Z -scores were <−2 SD. The prevalence of malnourished children was 25.2% at diagnosis and remained almost the same at the end of treatment. The odds of having a poor outcome (death and relapse) was higher among malnourished children and more so among stunted children with an odds ratios=2.15; 95% confidence interval, 0.5-8.3 and odds ratio=2.63; 95% confidence interval, 0.6-11.5, respectively. Although there was a trend showing worse outcomes in malnourished children with ALL at diagnosis when compared with well-nourished children larger studies using additional tools like arm anthropometry need to be conducted to prove the association. Abstract : Supplemental Digital Content is available in the text.